A Balaton térség imázsa a helyi lakosság szemszögéből – a fiatal népesség véleménye - Lőrincz, Katalin; Lang, Letícia; Banász, Zsuzsanna (Modern Geográfia, 2019)
The subject of the study is the region of Balaton Lake, because the development of the image of settlements and receptive areas and the involvement of the local population is becoming more and more important in the field of sustainable tourism development and tourism management. The purpose of this research is to map the image of the Balaton region, especially among the local young population (52% of the respondents are less than 35 years old) and the owners of second homes and holiday homes. Our research questions are the follows: considering typically local residents of the Balaton region (i) which settlements of this region are the most attractive, (ii) what they think first about the name of the settlement and Lake Balaton, (iii) what are they most proud of in the settlement and in the Balaton? The study is based on a primary questionnaire survey, which was conducted in 2018 and resulted a sample of 844 people. Based on the results – in response to the research question – the following findings can be made: considering typically local residents of the Balaton region (i) Balatonfüred, then Tihany and Siófok are the most attractive settlements, (ii) the name of the settlement reminds them of the characteristics of the settlement, and the name of the Balaton reminds them of their summer experiences, (iii) they are most proud of characteristics of the settlement and the natural recourses of Balaton region.